2019
DOI: 10.1136/bmjopen-2019-031624
|View full text |Cite
|
Sign up to set email alerts
|

Health and wellbeing of people with intellectual disability in New South Wales, Australia: a data linkage cohort

Abstract: PurposePeople with intellectual disability (ID) experience high rates of physical and mental health problems, while access to appropriate healthcare is often poor. This cohort was established to develop an epidemiological profile related to the health, health service use, disability services, mortality and corrective services records of people with ID.ParticipantsThe cohort contains 92 542 people with ID (40% females) with a median age of 23 years (IQR: 12–43 years) and 2 004 475 people with a neuropsychiatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(81 citation statements)
references
References 19 publications
1
77
0
1
Order By: Relevance
“…Data are drawn from a broader linkage infrastructure (Reppermund et al 2019) examining the epidemiological profile of people with neuropsychiatric disorders in NSW. It contains a near whole of NSW population sample of individuals with ID (n = 92 542), 1.13% of the NSW population in calendar year 2015 that falls within the 1-2% of the adult population estimated to have an ID (Wen 1997;Maulik et al 2011;Bourke et al 2016).…”
Section: Study Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data are drawn from a broader linkage infrastructure (Reppermund et al 2019) examining the epidemiological profile of people with neuropsychiatric disorders in NSW. It contains a near whole of NSW population sample of individuals with ID (n = 92 542), 1.13% of the NSW population in calendar year 2015 that falls within the 1-2% of the adult population estimated to have an ID (Wen 1997;Maulik et al 2011;Bourke et al 2016).…”
Section: Study Populationsmentioning
confidence: 99%
“…A key strength of the linked administrative data in this study is both the near population size sample of the ID population in NSW (Reppermund et al 2019) and the linking of health services and disability support services data together with data from corrective services. That 4.3% of the adult custody population was identified as having an ID reinforces previous work finding that there is an over-representation of ID in custody (Hayes et al 2007;Søndenaa et al 2008).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Compared with the general population, those with ID have poor physical and mental health. 2 , 3 , 4 In addition, ID has been associated with shorter life expectancy of up to 2 decades and low mean age at death, 5 , 6 although the mortality discrepancy between those with ID and the general population has decreased in the past decades. 5 The increase in mean age at death in ID may illustrate the improvements in policies and practices, including the deinstitutionalization initiated in many high-income countries during the 1970s and 1980s that eventually led to the complete closure of large institutions in Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that speech function disorder can have a diagnostic value as an early symptom in such conditions as organic brain damage [12], complex disorders of the nervous system development [3], and mental retardation [13][14][15].…”
mentioning
confidence: 99%